Reform of the Judicial Review System: Evaluation of the Constitutional Court's Authority in Maintaining Constitutional Supremacy - Harlina Hamid; Nurasia Natsir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study evaluates the effectiveness of the Constitutional Court’s authority in reviewing laws and regulations as a means of upholding constitutional supremacy in Indonesia. Employing both normative and empirical legal research methods, it examines the Constitutional Court’s rulings from 2019 to 2024 and assesses their broader implications for the national constitutional system. The findings reveal several structural weaknesses in the review mechanism, particularly related to the enforcement of decisions and the existence of dualism between the Constitutional Court and the Supreme Court in conducting judicial reviews. These shortcomings have created inconsistencies and reduced the optimal impact of the Constitutional Court’s role. To address these issues, the research recommends comprehensive reforms, including the unification of judicial review authority, enhancement of the Constitutional Court’s executorial powers, and expansion of public access to constitutional review procedures. Such measures are expected to strengthen the Court’s role as the guardian of the constitution, improve legal certainty, and support the creation of a more coherent and harmonious legal system in Indonesia.